Female Sexual Dysfunction: A Case Study of Disease Mongering and Activist Resistance - Tiefer, Leonore (PLoS Medicine, 2006)
"Tiefer highlights key steps in the ""creation"" of a new diagnosis, female sexual dysfunction, and of the campaign to challenge its reductionist approach to women's sexual problems. "
Number: 4
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; inégalités; patriarcat; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Women artists at the millennium - Armstrong, Carol M.; Zegher, M. Catherine de (MIT Press, 2006)
"More than thirty years after the birth of the modern women's movement and the beginnings of feminist art-making and art history, the time is ripe to examine the legacies of those revolutions. In Women Artists at the Millennium, artists, art historians, and critics examine the differences that feminist art practice and critical theory have made in late twentieth-century art and the discourses surrounding it. In 1971, when Linda Nochlin published her essay "Why Have There Been No Great Women Artists?" in a special issue of Art News, there were no women's studies, no feminist theory, no such thing as feminist art criticism; there was instead a focus on the mythic figure of the great (male) artist through history. Since then, the "woman artist" has not simply been assimilated into the canon of "greatness" but has expanded art-making into a multiplicity of practices with new parameters and perspectives. In Women Artists at the Millennium artists including Martha Rosler and Yvonne Rainer reflect upon their own varied practices and art historians discuss the innovative work of such figures as Louise Bourgeois, Lygia Clark, Mona Hatoum, and Carrie Mae Weems. And Linda Nochlin considers changes since her landmark essay and looks to the future, writing, "We will need all our wit and courage to make sure that women's voices are heard, their work seen and written about."–Jaquette
OCLC: ocm62766150
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; art féministe; corps; cours; discours dominant; femmes* artistes; har4600; maternité; premier cycle; périodes historiques; représentation; sexisme; systèmes d'oppressions; thématiques

The Cyborg Embryo: Our Path to Transbiology - Franklin, S. (THEORY CULTURE AND SOCIETY, 2006)
It is useful on the occasion of the 21st anniversary of the ‘Cyborg Manifesto’ not only to reconsider its lessons in the context of what is frequently described as the re-engineering of ‘life itself’, but to look at Haraway’s earlier work on embryos. In this article I begin with Haraway’s analysis of embryology in the 1970s to suggest her cyborg embryo was already there, and has, if anything, gained relevance in today’s embryo-strewn society. I argue further, as the title suggests, that the cyborg embryo has been crucial in defining our path to what I am calling here, building on Haraway’s notion of trans from Modest_Witness, ‘transbiology’ - broadly meaning stem cell research, cloning, tissue engineering and regenerative medicine. To illustrate this argument I draw on recent ethnographic fieldwork in a new stem cell derivation facility in the UK built adjacent to an IVF surgery. Using this example, I explore the important and paradoxical role of IVF in the emergence of stem cell science, cloning and transbiology, suggesting that Haraway’s analysis remains crucial to understanding the ironic and contradictory, and unexpectedly generative, circumstances through which the IVF-stem cell interface - the door to transbiology - came into being.
Keywords: approches et analyses; biologie; care; corps; cours; discipline; discours dominant; fecondation in vitro; féminisme cyborg; justice reproductive; lit4700; maternité; premier cycle; ressource en ligne; santé; sciences; sciences humaines; sociologie; systèmes d'oppressions; thématiques

S’approprier son corps et sa santé. Entretien avec Rina Nissim - Fussinger, Catherine; Rey, Séverine; Vuille, Marilène (Nouvelles Questions Feministes, 2006)
Parmi les personnes qui ont réellement fait avancer les choses et apporté des changements dans la vie de beaucoup de femmes, il y a Rina Nissim qui a oeuvré depuis son engagement au sein du MLF de Genève au début des années 1970 pour que les femmes se réapproprient leur corps et leur santé. Ce numéro de « Nouvelles Questions féministes » sur la santé consacre une bonne partie de ses pages à une discussion avec Rina Nissim. Cette militante du groupe « avortement » et self-help » du MLF genevois raconte comment elle est passée de l'école d'infirmière à une vie de militantisme et de voyages, avec la naturopathie pour bagage. Publiant des ouvrages sur la santé des femmes ayant eu un succès important tel que « Mamamélis », cette pionnière en Suisse ouvre le « dispensaire des femmes »fonctionnant sur un mode autogéré, suite à un voyage aux États-Unis, avec d'autres femmes infirmières psychologues et médecins. Les femmes vont alors trouver une alternative aux rapports de pouvoirs classiques des relations médecin-patient et aux médicaments traditionnels, dans un mouvement de prise de conscience et d'action sur leur propre corps. L'engagement international de Rina, en Amérique Central et en Inde principalement où elle s'installe cinq ans et coordonne différents projets, aura permis a de nombreuses femmes de se découvrir elles-mêmes et les autres, de se débarrasser de la honte et se rendre compte que la maladie est souvent liée à un positionnement social.
Number: 2 Publisher: Éditions Antipodes
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique centrale; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; europe; france; inde; justice reproductive; premier cycle; périodes historiques; racisme; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; suisse; systèmes d'oppressions; thématiques; travail; états-unis

Médicalisation de la ménopause, mouvements pour la santé des femmes et controverses sur les thérapies hormonales - Löwy, Ilana; Gaudillière, Jean-Paul (Nouvelles Questions Feministes, 2006)
Le traitement hormonal de la ménopause, présenté entre 1970 et 2000 par la majorité des experts comme capable d’accroître le bien-être des femmes mais aussi de prévenir des nombreuses pathologies liées au vieillissement féminin, a été déclaré en 2002 inutile et dangereux suivant un essai clinique nord américain, Women’s Health Initiative (WHI). En voie de conséquence, les prescriptions de ce traitement ont chuté dramatiquement entre 2002 et 2005. Cet article retrace les origines féministes de WHI, puis suit les conséquences de la publication de ses résultats aux États-Unis, en France et en Allemagne. En conclusion, il revient sur les tensions entre les rôles des femmes comme utilisatrices des hormones, comme expertes et comme militantes des mouvements pour la santé des femmes.
Number: 2 Publisher: Éditions Antipodes
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; allemagne; amérique du nord; amériques; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis